Inovasi Supervisi Akademik oleh Kepala Sekolah dalam Meningkatkan Kompetensi Guru: Tinjauan Literatur Sistematis - Siswanto, Siswanto (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to examine the role of academic supervision innovation by school principals in enhancing teacher competence through a Systematic Literature Review (SLR) approach. Teacher competence is a key factor in improving the quality of education, and the role of school principals as educational leaders is crucial in guiding and developing the professional skills of teachers. Innovations in academic supervision, which include new techniques in observation, mentoring, and evaluation of teaching, are expected to enhance the effectiveness of the learning process and the development of teacher competence. This review analyzes 15 journal articles published over the last 10 years, discussing various types of academic supervision innovations implemented by school principals and their impact on improving teacher competence. The findings from this literature review indicate that supervisory innovations carried out through collaborative approaches, constructive feedback, and reflective development can significantly enhance teachers' pedagogical and professional skills. However, challenges in implementing these innovations, such as time and resource constraints, as well as external factors, remain barriers to effective implementation. This study provides recommendations for school principals to focus more on supervisory strategies that are based on teacher self-development and continuous learning.